Measurement of Some Biochemical Parameters in Metabolic Syndrome - Ahmed , Suhair Abdul-Raheem; Ascar , Israa Fadhil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Patients with diabetes, high blood pressure (BP), and obesity have metabolic syndrome (MetS). The study aims to evaluate the levels of obestatin and osteopontin (OPN) as markers for detecting MetS and their relationship with other biomarker parameters at Al-Yarmuk Teaching Hospital in Baghdad. A total of 165 patients (125 with MetS and 40 healthy subjects as a control group) whose ages ranged from 20 to 80 years were examined and participated in this study. Body mass index (BMI), BP, fasting serum glucose (FSG), liver enzymes, total protein, and serum lipid profile were evaluated in each patient and control. In addition, obestatin and OPN were used with commercial ELISA kits according to the manufacturer’s instructions. The study’s results showed significant differences (p < 0.05) in BMI, blood pressure (BP), fasting serum glucose (FSG), liver enzymes, and lipid profile between the MetS and control groups. The levels of obestatin were notably decreased in the MetS group compared to the control group (280.8 pg/mL vs. 1082.1 pg/mL). The level of OPN in patients was significantly higher than in controls (17.96 ng/mL vs. 5.47 ng/mL), respectively. The receiver operating characteristic (ROC) curve tests for obestatin and OPN are 0.981 and 0.999, respectively, which indicate that Obestatin and OPN are considered good diagnostic markers for subjects with MetS. It can be proposed that decreased levels of obestatin and increased levels of OPN in obese individuals may contribute to the onset of MetS and disrupted lipoprotein metabolism.